2021
DOI: 10.3389/fpls.2021.617768
|View full text |Cite
|
Sign up to set email alerts
|

A Mobile NMR Sensor and Relaxometric Method to Non-destructively Monitor Water and Dry Matter Content in Plants

Abstract: Water content (WC) and dry matter content (DMC) are some of the most basic parameters to describe plant growth and yield, but are exceptionally difficult to measure non-invasively. Nuclear Magnetic Resonance (NMR) relaxometry may fill this methodological gap. It allows non-invasive detection of protons in liquids and solids, and on the basis of these measures, can be used to quantify liquid and dry matter contents of seeds and plants. Unfortunately, most existing NMR relaxometers are large, unwieldy and not su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 98 publications
2
28
0
Order By: Relevance
“…Similarly, more straightforward, sensor-like applications of mobile NMR have been demonstrated by using small scale NMR devices (NMR sensors; NMRS) as online sensors to measure changes in water content in growing trees and pods ( Rascher et al , 2011 ; Lechthaler et al , 2016 ). More recently, an NMRS coupled with relaxometric analysis was shown to enable the concurrent, real-time quantification of both solid and liquid matter in situ ( Windt et al , 2021 ). Using a custom designed C-shaped NMR magnet, NMR coil, and magnet housing, plant samples can be inserted into the NMRS to monitor the development of plant tissues through developmental stages with little to no impact on the tissue under investigation (see also: Windt and Blümler, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, more straightforward, sensor-like applications of mobile NMR have been demonstrated by using small scale NMR devices (NMR sensors; NMRS) as online sensors to measure changes in water content in growing trees and pods ( Rascher et al , 2011 ; Lechthaler et al , 2016 ). More recently, an NMRS coupled with relaxometric analysis was shown to enable the concurrent, real-time quantification of both solid and liquid matter in situ ( Windt et al , 2021 ). Using a custom designed C-shaped NMR magnet, NMR coil, and magnet housing, plant samples can be inserted into the NMRS to monitor the development of plant tissues through developmental stages with little to no impact on the tissue under investigation (see also: Windt and Blümler, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…This capacity gives unprecedented insight into the dynamics of tissue growth with potential to add significantly to our fundamental understanding of seed yield development in cropping systems. The NMRS enables the observation of diel variation in organ growth with high precision ( Rascher et al , 2011 ; Windt et al , 2021 ) facilitating the observation of growth rates across diurnal time scales and developmental processes. Using this approach, it has been shown that dry matter accumulation in reproductive tissues of wheat continues under dark conditions ( Windt et al , 2021 ), suggesting that processes such as starch remobilization and phloem transport supply photoassimilates for tissue maintenance and growth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…67,68 This is a useful approach to evaluate the crystalline state 69 and determine carbon chain lengths of fatty acid mixtures. 70 As a result, NMR-based relaxometry is widely used in various industries and research elds such as plants, 71 point-of-care testing, 72 food 73,74 and materials. 75,76 For the characterization of constituents in complex materials using low-resolution NMR relaxometry data, Laplace inversion using sparse representation methods has been applied.…”
Section: Global Human Population Growth and Sustainable Developmentmentioning
confidence: 99%
“…2d, the leaf dry matter content of T3 was significantly higher than that of T1 and T2 (p < 0.01), but there was no a significant difference between T1 and T2. Leaf dry matter content can reflect the adaptability of leaves to arid climates, and is the most stable variable on the axis of resource acquisition [49]. Leaf dry matter content is the preferred index in plant ecology research, and it can be a good indicator of the plant's ability to preserve nutrients [43,50].…”
Section: Response Of Leaf Functional Traits To Urban Atmospheric Particulate Mattermentioning
confidence: 99%